Satisfactions for hearing aid usage in Chiang Mai University Hospital - Sestawanich, Natthanin; Kaewsiri, Suwicha Isaradisaikul; Boonyanukul, Sriton (Biomedical Sciences and Clinical Medicine, 2013)
Objectives To study satisfactions for hearing aid usage and factors effecting their satisfactions Materials and methods Evaluation 6 factors of satisfaction with a 28-item questionnaire between July 1 and December 31, 2012 in 60 patients with 40-90 decibel hearing loss who received hearing aids from Chiang Mai University Hospital. Data was analyzed, using descriptive statistic for evaluation satisfaction scores in each factor of hearing aid usage and multiple regression analysis (correlation coefficient) for evaluation factors effecting their satisfactions. Results The hearing aid users were 30 men and 30 women. Average age was 68 years. Seventy- five percent of those have never been used a hearing aid. Average air-conduction threshold in the hearing aid fitted-ears were 67.1 decibels. The overall average score of satisfactions for hearing aid usage in Chiang Mai University Hospital were in high level (3.55). In each factor, the average score of cosmetic factor (3.58), of communication benefit factor (3.52), of ease of use factor (4.10) and of cost and maintenance factor (3.68) were in high level. The average score of acoustic factor (3.48), of comfortable factor (3.48) were in moderate level. Factors significantly effecting satisfaction (p <0.05) were 1)aging effecting cosmetic, communication benefit and ease of use factor , 2) income effecting sound quality factor, 3) hearing aid style effecting cost and maintenance factor, 4) numbers of family member effecting comfortable factor and 5) SD score gain effecting cost and maintenance factor. Conclusion Overall satisfactions for hearing aid usage in Chiang Mai University Hospital were in high level. Factors effecting satisfaction as follows aging, income, hearing aid style, numbers of family member and SD score gain.